PENGARUH MODEL PROBLEM BASED LEARNING BERBANTUAN MEDIA WORD SEARCH PUZZLE TERHADAP KETERAMPILAN KOMUNIKASI ILMIAH PESERTA DIDIK KELAS X FASE E DI SMAN 1 KOTANOPAN - Aminah Lubis, Ummi; Alberida, Heffi; Arsih, Fitri; Olvia Rahmi, Fitri (Jurnal Biogenerasi, 2024)
The aim of this research is to determine the effect of the model Problem Based Learning Media assisted Word Search Puzzles on the scientific communication skills of class X Phase E students at SMAN 1 Kotanopan. This research is an experimental research design Randomized Control Group Posttest Only Design. Sampling using techniques deliberate sampling namely sampling based on certain criteria. Class X-1 is the experimental class and class X-3 is the control class. The data analysis technique used is test independent sample t-test The prerequisite tests are first carried out, namely the normality test and homogeneity test. The research results showed that the scientific communication skills of students in the experimental class were higher than those in the control class. The results of the hypothesis test show a significance value of 0.021<0.05. So it can be concluded that the application of the model Problem Based Learning media assisted Word Search Confusing has a positive effect on students' scientific communication skills.